High Mobility Group Box 1 and Interleukin 6 at intensive care unit admission as biomarkers in critically ill COVID-19 patients - Sivakorn, C; Dechsanga, J; Jamjumrus, L; Boonnak, K; Schultz, MJ; Dorndorp, AM; Phumratanaprapin, W; Ratanarat, R; Naorungroj, T; Wattanawinitchai, P; Siripoon, T; Duangdee, C; et al. (American Society of Tropical Medicine and Hygiene, 2021)
Exuberant inflammation manifesting as a “cytokine storm” has been suggested as a central feature in the pathogenesis of severe coronavirus disease 2019 (COVID-19). This study investigated two prognostic biomarkers, the high mobility group box 1 (HMGB1) and interleukin-6 (IL-6), in patients with severe COVID-19 at the time of admission in the intensive care unit (ICU). Of 60 ICU patients with COVID-19 enrolled and analyzed in this prospective cohort study, 48 patients (80%) were alive at ICU discharge. HMGB1 and IL-6 plasma levels at ICU admission were elevated compared with a healthy control, both in ICU nonsurvivors and ICU survivors. HMGB1 and IL-6 plasma levels were higher in patients with a higher Sequential Organ Failure Assessment (SOFA) score (> 10), and the presence of septic shock or acute kidney injury. HMGB1 and IL-6 plasma levels were also higher in patients with a poor oxygenation status (PaO2/FiO2 < 150 mm Hg) and a longer duration of ventilation (> 7 days). Plasma HMGB1 and IL-6 levels at ICU admission also correlated with other prognostic markers, including the maximum neutrophil/lymphocyte ratio, D-dimer levels, and C-reactive protein levels. Plasma HMGB1 and IL-6 levels at ICU admission predicted ICU mortality with comparable accuracy to the SOFA score and the COVID-GRAM risk score. Higher HMGB1 and IL-6 were not independently associated with ICU mortality after adjustment for age, gender, and comorbidities in multivariate analysis models. In conclusion, plasma HMGB1 and IL6 at ICU admission may serve as prognostic biomarkers in critically ill COVID-19 patients.